PROFILE OF ELEMENTARY SCHOOL TEACHER IN CONCEPT UNDERSTANDING OF GEOMETRY - Samuel Igo Leton; Kristoforus Djawa Djong; Irmina Veronika Uskono; Wilfridus Beda Nuba Dosinaeng; Meryani Lakapu (IKIP Siliwangi and I-MES, 2020)
Students need teachers with a deep understanding of mathematical concepts to improve their mathematical knowledge and achievement. The observation results of several elementary school teachers showed that they still have a lack of understanding of the geometry concepts. This research is an exploratory study with a qualitative approach that aims to describe the performance of elementary school teachers in understanding the concepts of triangles and squares. The participants in this study were elementary school teachers across Soe City District. A description test deals with the geometry concept of two-dimensional shapes that were implemented to determine the most appropriate teachers to participate in the study. Thirty-three teachers were then selected based on this preliminary test results. In-depth interviews were also conducted with the participants. The data analysis showed that the participants had a lack of understanding of the concept of two-dimensional shapes and necessary arithmetic skills. Moreover, the data suggested that the participants held various perceptions regarding their understanding of certain concepts based on their experience in teaching the mathematical concept. Based on these results, some programs are recommended to improve professionalism and pedagogical competencies, such as a refresher training program for basic mathematical material and training in teaching aids used. These programs are expected to help prepare elementary school teachers in teaching mathematics.